Formation of Tolerance as Preventive Measure of Xenophobia And Extremism among the Students - Fedoseeva, Irina Vladimirovna (Psychological Prospects Journal, 2012)
On the basis of theoretical analysis an attempt to widen and deepen the content of such concepts as «tolerance», «xenophobia», «extremism» is made in the article; expediency of the students’ tolerance formation in the higher educational establishments as a preventive measure in the overcoming of intolerance manifestation is proved, the main principles in the formation of tolerance as a person’s feature are revealed.